Antara Filsafat Dan Kalam Sebuah Kesalahfahaman Paradigmatik - Shofiyullah Mz (Al-Jami'ah Research Centre, 1998)
The emerging phenomenon of religiosity force us to make a reevaluation without neglecting our keen analysis. Recent religious discourse tends more on the repetition of some old discourses using “new Clothes” and gives only little constructive-subtantive information. It is understandable, therefore, that the jargons of “majority-minority” “minna-minhum”, “you-we” “right-wrong”, are still widely believed as the manifestation of the level of someone’s adherence to their religions. This condition seems to be valid for all religions, including Islam. In Islam, kalam and philosophy are the two important sources which have great access especially in constructing the mode of thought embodied in the daily activities of the ummah. The emergence of some sects in Islam including shī’ah, Mu’tazilah, Jabariah and Sunni as well as the easy judgment given each other by, and for, the philosopher and the ologians as the unbelives clearly show how was the political conflict of that time. This interest was then neatly covered by the “religious robe” which, in trun, leaved an unpleasant attitude for the next generations. Thus, the research on Islamic becomes closed and is no longer opened. It would be more ironic when one realizes that historical interpretations of the Qur’an and the Hadith are believed as the facts themselves which are free from mistakes. In responds to this phenomenon, there emerges a new critical thought which tries to be neutral in understanding some aspects of these products of thought. The type of the relationship between the doctrinal, theological, historical-empirical and critical -philosophical. This alternative is, so far, considered as the most appropriate one although it does not escape some problems. To mention but few are the apriori attitude and the intellectual arrogance which might blur the problems. This article is aimed as another alternative to deal with the Problems.